2008
DOI: 10.1080/00015458.2008.11680269
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Leakage of a Colorectal Anastomosis Treated by Transanal Endoscopic Microsurgery

Abstract: We describe a possible minimally invasive technique to avoid laparotomy and/or the creation of a derivative stoma in the management of anastomotic leakage. Hospital stay is not significantly prolonged, future reïntervention for closure of stoma is avoided and sphincter function is preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
1
5
0
2
Order By: Relevance
“…These indications are known as ''atypical,'' as they do not involve the excision of rectal adenoma or carcinoma [33]. The atypical indications in our study is comparable to others reported that describes the indications in pelvic abscess, benign rectal stenosis, gastrointestinal stromal tumor, rectal prolapse, extraction of impacted fecaloma at the rectosigmoid junction and presacral tumor [34][35][36][37][38]. In recent years, TEM via natural orifices (natural orifice transluminal endoscopic surgery: NOTES) has been used to gain access to the peritoneal cavity and to perform intraabdominal procedures [39][40][41].…”
Section: Discussionsupporting
confidence: 75%
“…These indications are known as ''atypical,'' as they do not involve the excision of rectal adenoma or carcinoma [33]. The atypical indications in our study is comparable to others reported that describes the indications in pelvic abscess, benign rectal stenosis, gastrointestinal stromal tumor, rectal prolapse, extraction of impacted fecaloma at the rectosigmoid junction and presacral tumor [34][35][36][37][38]. In recent years, TEM via natural orifices (natural orifice transluminal endoscopic surgery: NOTES) has been used to gain access to the peritoneal cavity and to perform intraabdominal procedures [39][40][41].…”
Section: Discussionsupporting
confidence: 75%
“…Such efforts are best done in the lateral and posterior portions of the extraperitoneal rectum. 10,11 TEM has been used to repair an anastomotic leak 12 and to excise retrorectal tumors. 13,14 TEM has been used in a hybrid manner with other minimally invasive technology.…”
Section: Indicationsmentioning
confidence: 99%
“…The technique presents the advantage of a perfect view of the operating field, thus enabling the extraluminal mass to be distinguished and an adapted rectotomy to be performed with good hemostatic control. It allows placement of a drain (e.g., a Foley catheter) in the cavity for drainage and irrigation [41,44].…”
Section: Pelvic Abscessmentioning
confidence: 99%